Hubungan Imunisasi Dasar Lengkap dengan Kejadian Stunting pada Balita di Wilayah Kerja UPT Puskesmas Batu Aji Kota Batam - Eflin Elianora Betaria Pasaribu; Nelli Roza; Huzaima Huzaima; Yunisa Friscia Yusri (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Background: Globally, stunting in children under five years old in 2022 is around 22.3% or 148 million children under 5 years old. In Southeast Asia alone, the prevalence of stunting is 26.4% or 14.4 million. Objective: This study was to determine the correlation complete basic immunization and the incidence of stunting in toddlers in the Working Area of UPT Puskesmas Batu Aji Batam City. Methods: This research is a quantitative study observational analytic design with a case control approach. The sample is 42 toddlers and using purposive sampling technique. Data collection tools use observation sheets and the chi-square test. Findings: The results of the chi square statistical test obtained a p-value of 0.005 <0.05 (OR = 6.400 (95% CI (1.654 - 24.770)). There is a significant relationship between complete basic immunization and the incidence of stunting in toddlers in the Working Area of UPT Puskesmas Batu Aji Batam City. Implication: Complete basic immunization has a significant impact on the growth and development of toddlers